The analysis of the prevalence of strategic management accounting techniques and the level of development of the cost system in large companies in Bosnia and Herzegovina - Srđan Lalić; Amra Gadzo; Benina Veledar (Anali Ekonomskog fakulteta u Subotici, 2020)
The paper has two research goals. The first goal is to investigate the prevalence of certain techniques of strategic management accounting in large companies in Bosnia and Herzegovina (hereinafter BiH), while the second research goal is to analyze the dependence of the number of strategic management accounting techniques used and the degree of development of the cost system in the company. For the purposes of this research, we collected survey questionnaires from 110 large companies based in BiH. The results of the research show that the three most common techniques of strategic management accounting in large companies in BiH are: Quality Costing (52.73%), Strategic Pricing (51.82%) and Benchmarking (50.91%), while the least common techniques are: Life Cycle Costing (11.82%), Attribute Costing and Integrated Performance Management Systems (with 12.73% each), and Activity Based Costing/ Management (17.27%). One-way analysis of variance (ANOVA) tested the differences in the number of strategic management accounting techniques used and the level of development of the cost system in companies. Companies that applied on average two techniques of strategic management accounting belonged to the first level of development, those that applied on average four techniques belonged to the second level of development, while companies that have the third level of cost system development on average applied six techniques of strategic management accounting. There were no companies in the sample with the fourth and fifth level of development of the cost system.